Case of Gonorrheal Urethritis and Post-Traumatic Stress Disorder Due to Sexual Abuse in a Boy - Qaira Anum; Satya Wydya Yenny; Vesri Yossy; Fauzana Nazifah (Faculty of Medicine, Universitas Padjadjaran, 2026)
Sexual violence against children and the occurence of sexually transmitted infections (STIs), particularly gonorrheal urethritis, are rare in the pediatric population. This case report describes an 8-year-old boy who acquired a sexually transmitted infection uncommon for his age group, suggesting the possibility of an unusual underlying issue requiring further evaluation and management. This boy presented with a history of genital-to-genital sexual contact with a female peer 10 days prior. He was diagnosed with acute uncomplicated gonococcal urethritis, presenting with symptoms of painful urination and yellowish-white discharge from the genital area that had progressively worsened over the preceeding week. The patient also exhibited signs of post-traumatic stress disorder, including frequent crying and low self-esteem. Venereological examination revealed thick yellowish-white discharge at the external urethral orifice. Gram staining demonstrated intracellular gram-negative diplococci with >30 polymorphonuclear cells per high-power field, and culture confirmed the presence of Neisseria Gonorrhoeae. The patient was treated with oral erythromycin 250 mg four times daily for one week. He also received psychoeducational therapy and psychopharmacological treatment, including fluoxetine (6 mg once daily), vitamin B1 (2 mg once daily), and folic acid (2 mg once daily), administered by the Department of Child and Adolescent Psychiatry of Dr. M. Djamil General Hospital. Evaluation of the patient on the seventh day after therapy showed good outcomes. Early diagnosis and proper management of gonococcal urethritis cases are essential to reduce the incidence of complications and to address potential psychosocial concerns.